2012
DOI: 10.2214/ajr.10.6272
|View full text |Cite
|
Sign up to set email alerts
|

Background Parenchymal Enhancement on Breast MRI: Impact on Diagnostic Performance

Abstract: Increased background parenchymal enhancement on breast MRI is associated with younger patient age and higher abnormal interpretation rate. However, it is not related to significant differences in positive biopsy rate, cancer yield, sensitivity, or specificity of MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(113 citation statements)
references
References 19 publications
6
102
2
1
Order By: Relevance
“…It is in contrast with a study conducted by DeMartini W B et al (12), who found that background parenchymal enhancement were significantly more extensive than older women in younger women.…”
Section: Discussioncontrasting
confidence: 97%
“…It is in contrast with a study conducted by DeMartini W B et al (12), who found that background parenchymal enhancement were significantly more extensive than older women in younger women.…”
Section: Discussioncontrasting
confidence: 97%
“…7 The "degree" of BPE is linked to the risk of developing breast cancer, may affect the reading of breast MRI, the staging and the risk of cancer and even the long-term outcome, particularly in patients with certain subtypes at immunohistochemistry. [8][9][10][11][12][13][14][15] BPE can be visually assessed qualitatively using the Breast Imaging-Reporting and Data System (BI-RADS) scores or quantitatively using software. 7,16 However, radiologist agreement for BPE qualitative evaluation is fair 17 and, to the best of our knowledge, there is a lack of uniformity on quantitative measurements of BPE on breast MRI.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, BPE associated with BI-RADS scores in all women, including premenopausal ones and women aged 30 -39 years. De Martini et al reported that abnormal interpretation rates for women with moderate or marked BPE were significantly higher than that for women with minimal or mild BPE, but positive biopsy rates were not affected by different BPE [13]. However, in a study by Hambly in women with minimal BPE, no significant difference in BI-RADS category for women with mild, moderate, or marked BPE was found [4].…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the De Martini et al study [13], we considered the relationships between BPE and the menopausal status variable. Almost quarter of our subjects underwent short-interval follow-ups and rates of short-interval follow-ups did not associate with BPE; these results are in contrast to the previous Hambly study [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation